Analysis of the machine-building sector in Ukraine and generation of the factor characteristics for the evaluation of the enterprise management effectiveness - Kolinko, Natalia (Technology audit and production reserves, 2016)
The article is devoted to the analysis of the machine-building sector in the structure of the industrial complex of Ukraine. The statistical analysis of its dynamics allows to form a number of factors of external and internal environment, which are to form the basis for multifactorial regression models aimed to evaluate the efficiency of theenterprise management.The statistics on the innovative activity of the machine-building sector in Ukraine and Lviv region, according to the State Statistics Service of Ukraine, helps to assess economic conditions for innovative activity of the enterprises. The staged sequence of research of the external and internal factors influence on the economic results of the machine-building enterprise are revealed as a result of the initial data analysis. The conducted research will lay in the basis of the numerical model, aimed to evaluate the efficiency of the machine-building enterprise management.